2007
DOI: 10.1136/jnnp.2007.117655
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of subarachnoid haemorrhage: a systematic review with emphasis on region, age, gender and time trends

Abstract: Background and aim: To update our 1996 review on the incidence of subarachnoid haemorrhage (SAH) and assess the relation of incidence with region, age, gender and time period. Methods: We searched for studies on the incidence of SAH published until October 2005. The overall incidences with corresponding 95% confidence intervals were calculated. We determined the relationship between the incidence of SAH and determinants by means of univariate Poisson regression. Results: We included 51 studies (33 new), descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
652
9
33

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,035 publications
(731 citation statements)
references
References 76 publications
37
652
9
33
Order By: Relevance
“…One hypothesis for this is based on the fact that with the decrease in plasma levels of sex hormones in post menopausal women, there would be an inhibition of collagen formation, and thus can affect the brain blood vessels. 10,11 The point prevalence of multiple aneurysms in our series was 26%, falling between the average suggested by the literature, 17% to 30%. Studies say that the prevalence of multiple aneurysms changes according to the prevalence of risk factors for aneurysm formation in various populations.…”
Section: Discussionsupporting
confidence: 49%
“…One hypothesis for this is based on the fact that with the decrease in plasma levels of sex hormones in post menopausal women, there would be an inhibition of collagen formation, and thus can affect the brain blood vessels. 10,11 The point prevalence of multiple aneurysms in our series was 26%, falling between the average suggested by the literature, 17% to 30%. Studies say that the prevalence of multiple aneurysms changes according to the prevalence of risk factors for aneurysm formation in various populations.…”
Section: Discussionsupporting
confidence: 49%
“…In humans, aneurysms occur more often in women (70–75%) pre‐ and postmenopause 2. However, aneurysm ruptures occur most often in postmenopausal women 3, 4…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen deficiency has been linked to aneurysm formation and rupture. Approximately 70% to 75% of aneurysms occur in women,2 with postmenopausal women having the highest risk for aneurysm rupture 3, 4. Several studies have investigated estrogen deficiency and CA5, 6, 7, 8; however, the mechanism remains unknown.…”
mentioning
confidence: 99%
“…One such population, with a higher rate of IA incidence, is the thoroughly characterized genetic isolate of Finland. [35] A recent study revealed four novel low-frequency risk loci utilizing an alternative genetic approach. [36] The study focused on the Finnish population, enriched the percentage of familial IA patients in the discovery sample, and increased genome-wide coverage through imputing genotyped variants against the 1000 genomes project reference panel (v3, March 2012 release).…”
Section: Mediators Of Inflammationmentioning
confidence: 99%